2018
DOI: 10.3389/fphys.2018.00377
|View full text |Cite
|
Sign up to set email alerts
|

Association Between TERT rs2736098 Polymorphisms and Cancer Risk-A Meta-Analysis

Abstract: Background: Cancer remains a leading cause of death and constitutes an enormous burden on society worldwide. The association between the human telomerase reverse transcriptase (TERT) gene variant rs2736098 polymorphisms and cancer predisposition remain inconclusive.Objective and methods: Databases including Pubmed and Embase were systematically searched from inception to September 15, 2017 to retrieve studies investigating the association between the TERT variant rs2736098 polymorphisms and cancer risk in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In a study conducted by Zhou et al, [19] , subgroup analysis based on cancer type indicated that the TERT rs2736098 (G>A) polymorphism was associated with HCC, the heterozygous and dominant genetic models supported an increased cancer susceptibility in the population carrying the rs2736098 A allele (GA vs. GG: OR=1.595, 95% CI=1.246-2.042, p=0.000; and GA/AA vs. GG: OR=1.494, 95% CI=1.123-1.987, p=0.006) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Zhou et al, [19] , subgroup analysis based on cancer type indicated that the TERT rs2736098 (G>A) polymorphism was associated with HCC, the heterozygous and dominant genetic models supported an increased cancer susceptibility in the population carrying the rs2736098 A allele (GA vs. GG: OR=1.595, 95% CI=1.246-2.042, p=0.000; and GA/AA vs. GG: OR=1.494, 95% CI=1.123-1.987, p=0.006) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis has revealed an association between the allele A at TERT rs2736098 G > A (located on 5p15.33) and cancer development. Besides, the ethnicity-specific effect has also been found while analyzing different subgroups [ 67 ]. Another meta-analysis has shown that allele C at TERT - CLPTM1L rs401681 (located on 5p15.33) was a low-penetrance risk allele for the development of lung, bladder, prostate cancers, and basal cell carcinoma but also a potential protective allele for melanoma and pancreatic cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, several meta-analyses have revealed the relationship between TERT rs2736098 polymorphism and cancer risk, and previous studies have shown that rs2736098 leads to the occurrence and development of cancer. [20][21][22] However, there is no specific study on lung cancer. Thus, this meta-analysis was performed by including case-control studies to examine the above possible relationship of TERT rs2736098 polymorphism with the lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%